Mini‐hyper CVD + CRIB (condensed rituximab, inotuzumab ozogamicin, and blinatumomab) for refractory pediatric B‐acute lymphoblastic leukemia. Issue 1 (28th August 2022) - McCall, David; Jabbour, Elias; Roth, Michael; Nunez, Cesar; Cuglievan, Branko
Abstract: Relapsed or refractory pediatric patients with B‐acute lymphoblastic leukemia (B‐ALL) have high rates of toxicities and relapse, and novel therapy is needed. We present a case of a 5‐year‐old male child with high‐risk B‐ALL that was refractory to several re‐induction regimens. He was put into minimal residual disease‐negative remission after re‐induction with chemotherapy plus overlapping rituximab, inotuzumab ozogamicin, and blinatumomab, termed mini‐hyper‐CVD (cyclophosphamide, vincristine, and dexamethasone) plus CRIB (condensed rituximab, inotuzumab ozogamicin, and blinatumomab). This regimen was well tolerated, and he received his transplant and engrafted with no significant infections, toxicities, or sinusoidal obstruction syndrome. This is the first reported use of a condensed sequential immunotherapy/chemotherapy regimen in a pediatric leukemia patient.